A Supportive-Educational Intervention for Heart Failure Patients in Iran: The Effect on Self-Care Behaviours - Vahid Zamanzadeh; Leila Valizadeh; A. Fuchsia Howard; Fatemeh Jamshidi (Nursing Research and Practice)
Background. Chronic heart failure is a major health and social problem. The promotion of self-care behaviours can potentially assist patients to effectively manage this chronic condition and prevent worsening of the disease. Formal personalized educational interventions that provide support and take into consideration the cultural context are needed. Objective. The objective of this research was to evaluate the effect of a supportive-educational intervention on self-care behaviours of heart failure patients in Iran. Methods. This research was a prospective, randomized trial of a supportive-educational intervention. Eighty heart failure patients were randomly assigned to receive the supportive-educational intervention or usual care. The intervention consisted of a one-hour, nurse-led, in-person education session and postdischarge followup by telephone over three months. Data were collected at baseline, one, two, and three months. Results. The control and intervention groups did not differ in self-care scores at baseline (P>0.05). Each of the self-care scores was significantly higher in the intervention group than the control group at 1, 2, and 3 months (P<0.001). There were significant differences in self-care behaviours over the three months, among participants in the intervention group. Conclusion. This study provides support for the effectiveness of a supportive-educational intervention to increase self-care behaviours among Iranian patients suffering from chronic heart failure.